Dermoscopic assessment of periungual and genital warts treated by multiple modalities: a report - Ankad, Balachandra S.; Koti, Varsha R. (International Journal of Research in Dermatology, 2022)
Periungual and genital warts pose a therapeutic challenge to the treating clinician as there is lack of single curative treatment modality. All existing therapeutic options are associated with high rate of recurrence when employed alone. Here authors reported complete cure of periungual and genital warts that were treated by multiple approach consisting of mumps-measles-rubella vaccine, radiofrequency ablation and oral acitretin. Therapeutic response was assessed by dermoscopy which revealed specific patterns before and after treatment. There was no recurrence of lesions even after 1 year of follow-up period.